Two Visions: Young Poles and Germans on Well-Ordered Economy - Gardawski, Juliusz (Warsaw Forum of Economic Sociology, 2018)
The paper discusses the results of comparative research of the well-ordered economy carried out among Polish and German youth (aged 18–30). The study was conducted at the turn of 2016 and 2017 on representative samples of young people from both countries. The list of dominant preferences of young Germans and young Poles sheds light on issues of key importance for the economic order. The set of preferences dominating among German youth represents the vision of a market (competitive) economy with a strong emphasis on social aspects: employee participation in management and the pursuit of social equality. Poles value the market economy with protection of national capital against foreign capital competition and an emphasis on the need to modernise the economy. There are several differences between the preferences given by the respondents from eastern and western parts of Germany. On the contrary to what was to be expected, the former are more liberal than the latter. The visions of respondents from Eastern states resemble those expressed by the respondents from Poland. The latter part of this paper presents the typologies of the visions of well-ordered economy obtained through factor analysis. Polish respondents most often hold the vision of ‘developmental national employee-friendly market economy’ while German respondents most often hold an individualistic or open version of ‘ordered-liberalism’.